RITUAL MENGHANYUTKAN LANCANG DI KUANTAN SINGINGI PROVINSI RIAU - juswandi, juswandi (Jurnal Ilmu Budaya, 2012)
This writing attempts to show that the ritual of drifting off the boat is one tradition to drive away the magical power which causes various diseases to human beaings and plants in the regency of Kuantan Sengingi, Riau. The ritual is led by a shaman who will read charm to drive away the evil spirits. However, in reading the charm, the shaman will combine the elements of charm with the verses of Al-Quran and prayers to the propehet Muhammad, s.a.w.